Production of a Recombinant Vp1 Protein of the Chicken Anaemiavirus for the Development of an Enzyme-Linked Immunosorbent Assay - Mahgoub, Elhem Omer (2004)

(untitled)
VP1 gene is an important gene responsible for the expression of a protein that may facilitate the diagnosis of chicken anaemia virus (CAV) infection.The VP1 gene was cloned and expressed in prokaryotic expression vector pRSET–B.The VP1 protein expression in E. coli was achieved as a fusion protein containing an immunogenic epitope. The protein expressed was detected by anti-VP1 monoclonal antibody with an apparent molecular weight of 50 kDa. Batch fermentation was used to scale up production of the protein in E. coli.The recombinant VP1 protein was successfully expressed during high cell density culture. The use of tangential flow filtration (TFF) filtration step for dialysis and desalting increased both the specific activity and the final yield of the purified fraction.The protein expressed has been tested as an antigen for detection of antibody to CAV in infected chicken.An enzyme-linked immunosorbent assay (ELISA) applied for the detection of serum antibody to CAV.This test depends on the availability of CAV polyclonal antibodies present in convalescent chicken serum to react with the VP1 antigen adsorbed to the ELISA plate.When serum samples from infected chicken were tested,the sensitivity of the assay was found to be greater than 93.3%.Furthermore, the ELISA test requires serum samples to be diluted at 1:100 compared to 1:50 for commercial ELISA,an increase in the potential of non-specific background that could be contributed by proteins available in serum samples.In conclusion the indirect ELISA approach using VP1 fusion protein has many advantages. The results of the present study can be used as a basis for the development of a reliable ELISA assay for detection of CAV